PENGARUH PENERAPAN AKUNTANSI KEUANGAN DAERAH, PENERAPAN AKUNTABILITAS KEUANGAN, SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) KABUPATEN AGAM PROVINSI SUMATERA BARAT - Riani, Isty; Agusti, Restu; Ali, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to demonstrate empirically the area of financial accounting application, implementation and application of the system of financial accountability reporting against performance accountability of government agencies. The sample was head of the planning section, sub-section chief financial, chief of personnel (with the categorization rank / class of echelon III and IV) who served in Local Government Agencies located in Agam District Government, amounting to 54 people. Data collection techniques using a questionnaire filled out by each sample. To test the hypothesis of the study used multiple regression analysis with SPSS. Results of the study explained that the application of financial accounting area affect the accountability of agency performance in Agam District. This means that at SKPD Agam, performance accountability of each SKPD affected by the application of financial accounting area. application of financial accountability have a significant impact on performance accountability institutions in Agam District. That is the better application of financial accountability, the better accountability of agency performance in Agam District. accountability information system affect the agency's performance in Agam District. This means that at SKPD Agam, performance accountability of each SKPD influenced by the information system.Keywords: Accountability, Finance, Reporting and Performance.